Principium Iuris Patientium Sebagai Perlindungan Terhadap Hak Pasien Yang Terkena Stroke - Margareta, Maria (Universitas Sumatera Barat, 2023)
The legal relationship between a doctor and a patient, or generally called a legal relationship between a health service user and a health service provider, is legally based on an agreement which requires the service provider to provide optimal information while the user must also provide information openly. This article reviews the Princium Iuris Patientium as an important conceptual framework in protecting the rights of patients affected by stroke. This principle emphasizes the importance of patients' rights to autonomy, including the right to obtain comprehensive information about medical procedures and the right to provide informed consent. In the context of stroke patients, a good understanding of the Princium Iuris Patientium helps in maintaining patient privacy, avoiding unwanted medical procedures, and ensuring that patients have control over their care. This article highlights the relevance of these principles in the medical setting and the importance of applying them to ensure care that is ethical, dignified and appropriate to the needs of patients affected by stroke..